The relationship between direct predation and antipredator responses: a test with multiple predators and multiple prey. Issue 8 (22nd June 2017) - Creel, Scott; Dröge, Egil; M'soka, Jassiel; Smit, Daan; Becker, Matt; Christianson, Dave; Schuette, Paul
Abstract: Most species adjust their behavior to reduce the likelihood of predation. Many experiments have shown that antipredator responses carry energetic costs that can affect growth, survival, and reproduction, so that the total cost of predation depends on a trade‐off between direct predation and risk effects. Despite these patterns, few field studies have examined the relationship between direct predation and the strength of antipredator responses, particularly for complete guilds of predators and prey. We used scan sampling in 344 observation periods over a four‐year field study to examine behavioral responses to the immediate presence of predators for a complete antelope guild (dominated by wildebeest, zebra, and oribi) in Liuwa Plains National Park, Zambia, testing for differences in response to all large carnivores in the ecosystem (lions, spotted hyenas, cheetahs, and African wild dogs). We quantified the proportion that each prey species contributed to the kills made by each predator (516 total kills), used distance sampling on systematic line transects to determine the abundance of each prey species, and combined these data to quantify the per‐capita risk of direct predation for each predator–prey pair. On average, antelopes increased their vigilance by a factor of 2.4 when predators were present. Vigilance varied strongly among prey species, but weakly in response to different predators. Increased vigilance was correlated with reduced foraging in a similar manner for all prey species. The strength of antipredator response was not detectably related to patterns of direct predation ( n = 15 predator–prey combinations with sufficient data). This lack of correlation has implications for our understanding of the role of risk effects as part of the limiting effect of predators on prey.